1976
DOI: 10.1111/j.1365-2621.1976.tb01103.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Preferences for Vegetables Grown Under “Commercial” and “Organic” Conditions

Abstract: The present study was designed to provide experimental data which would bear on undocumented claims as to the superior flavor of so called “organic” or “natural” foods. Four vegetables (lettuce, green beans, broccoli greens, and carrots) were grown under three conditions: depleted soil (no additional fertilizer or pesticides); commercially fertilized (plus pesticides), and organically fertilized (manure, no pesticides). Fifty consumer subjects evaluated the four vegetables individually in separate sessions, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 2 publications
0
17
1
Order By: Relevance
“…These results do not confirm the findings of other authors who found that organic information had an overall positive effect (Kihlberg et al, 2005;Schutz & Lorenz, 1976), an effect on most (Johansson et al, 1999) or on one of the varieties (Caporale & Monteleone, 2004). Although the present findings are only indicative, they point in the same direction as Caporale and Monteleones' results, showing an effect on the least liked variety only.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…These results do not confirm the findings of other authors who found that organic information had an overall positive effect (Kihlberg et al, 2005;Schutz & Lorenz, 1976), an effect on most (Johansson et al, 1999) or on one of the varieties (Caporale & Monteleone, 2004). Although the present findings are only indicative, they point in the same direction as Caporale and Monteleones' results, showing an effect on the least liked variety only.…”
Section: Discussioncontrasting
confidence: 76%
“…The effect of organic production information on hedonic judgements was addressed in several studies (Caporale & Monteleone, 2004;Johansson et al, 1999;Kihlberg et al, 2005;Schutz & Lorenz, 1976). Generally, a positive effect of organic information on liking was observed.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Abstract factors such as beliefs about healthiness or the importance of social elements are as real to an individual when evaluating a product as characteristics that can be objectively measured, such as color or sugar content (Peryam, 1963;Schutz and Lorenz, 1976).…”
Section: Determinants Of Liking and Use Of Sweet Foodsmentioning
confidence: 99%
“…Recent research on the effects of different types of label information suggests the possibility that these messages may also influence the acceptability of products containing added MSG. Both Schutz and Lorenz (1976) and Johansson et al (1999) examined the impact of information about growing method on consumer preferences for organic and conventional vegetables. In both studies, relative to these same foods unlabelled, products labelled as organic generally showed increases in measures of preference.…”
Section: Introductionmentioning
confidence: 99%